Розширення асортименту та поліпшення якості хлібобулочних виробів з тритикале - Григоренко, Олена Віталіївна; Григоренко, Елена Витальевна; Hryhorenko, Olena (ТДАТУ, 2019)
UK: У статті досліджено можливість виробництва хліба з тритикалевого борошна із застосуванням поліпшуючих харчових добавок для покращення його хлібопекарських властивостей. Доведено ефективність дії додавання лимонної кислоти та гліцерину при замішуванні тіста з тритикалевого борошна, досліджено зміни якості продукції з використанням нетрадиційної борошняної сировини, проведено оцінку якості нової продукції за органолептичними властивостями та стандартними фізико-хімічними показниками якості. RU: В статье исследована возможность производства хлеба из тритикалевой муки с применением улучшающих пищевых добавок для повышения ее хлебопекарских свойств. Доказана эффективность действия добавок лимонной кислоты и глицерина при замесе теста из тритикалевой муки, исследованы изменения качества изделий из данного нетрадиционного мучного сырья, проведена оценка качества новой продукции по органолептическим свойствам и стандартным физико-химическим показателям качества. EN: The modern Ukrainian market of bakery products analysis shows that the assortment presented on is made, mainly, from a wheat and rye flour. Limit nature of the use of other types of flour, unconventional for bakery and pastry industries, is explained by unsatisfactory of structural, mechanical and organoleptic properties of bakery products and testifies to the necessity of application of making better food additions. Among the substances-regulators of acidity the leading place take organic acids and their natrium salts. It is expedient to use additions that are characterized economic and raw material availability (lemon and vinegar acids, citrate of natrium, acetate of natrium). As substances, apt at formation hydrogen connections, it is possible to apply polyols (in particular, glycerin). The use of offer additions gives an opportunity not only to improve quality of wares from a weak wheatflour but also from triticale. It is characterized by a higher food value and low cost comparatively with a wheatflour, have the neutral taste and smell, and also due to high productive potential of grain, unpretentiousness to the terms of growing, firmness to illnesses able to stabilize the production of food grain. As a result of researches the reasonable bakery products technology is worked out with the use of wheat and flour with subzero technological properties, the lemon acid and glycerin additions efficiency of action is well-proven at the premix of dough from a triticale flour, the products quality changes were investigated with addition of unconventional flour raw material, the new products quality value on organoleptic properties and standard physical and chemical quality indexes was conducted.
Расширение ассортимента и улучшение качества хлебобулочных изделий из тритикале
Assortment expansion and quality improvement of triticale bakery products
Keywords: хлібопекарське виробництво; кондитерське виробництво; асортимент; тритикале; хлібопекарські властивості; поліпшувачі; якість